Progress on advanced & smart materials in engineering and mathematics. vol 3 - Mustafa, Zaleha (Penerbit UTeM Press, 2025)
Progress on Advanced & Smart Materials in Engineering and Mathematics focuses on communicating knowledge on recent advancements in advanced and smart engineering materials that will be significant to future generations. This Volume 1 consists of chapters encompassing four engineering themes: 1) Advanced and Smart Materials for Engineering Applications, 2) Green and Sustainable Materials for Engineering Applications, 3) Materials Behavior & Mathematical Models for Engineering Applications, and 4) Advanced and Smart Processing Technology for Engineering Applications. Despite numerous books conveying knowledge and research findings for the keywords' Advanced Materials', 'Smart Materials,' 'Engineering Application' and Mathematical Behavior Models, none so far combines all those critical keywords in a single book. It is a pioneering book that provides comprehensive knowledge of new era materials (both advanced and smart materials) for engineering applications. It translates the distinctive, complex material's behavior into applicable mathematical models that are beneficial to scientists and engineers to actualize their function in various products and components.